The effect of repeated loading and freeze–thaw cycling on immature bovine thoracic motion segment stiffness. (October 2014) - Sunni, Nabeel; Askin, Geoffrey N; Labrom, Robert D; Izatt, Maree T; Pearcy, Mark J; Adam, Clayton J
There is growing interest in the biomechanics of "fusionless" implant constructs used for deformity correction in the thoracic spine; however, there are questions over the comparability of in vitro biomechanical studies from different research groups due to the various methods used for specimen preparation, testing and data collection. The aim of this study was to identify the effect of two key factors on the stiffness of immature bovine thoracic spine motion segments: (1) repeated cyclic loading and (2) multiple freeze–thaw cycles, to aid in the planning and interpretation of in vitro studies. Two groups of thoracic spine motion segments from 6- to 8-week-old calves were tested in flexion/extension, right/left lateral bending and right/left axial rotation under moment control. Group A was tested with continuous repeated cyclic loading for 500 cycles with data recorded at cycles 3, 5, 10, 25, 50, 100, 200, 300, 400 and 500. Group (B) was tested after each of five freeze–thaw sequences, with data collected from the 10th load cycle in each sequence. Results of testing showed that for Group A: flexion/extension stiffness reduced significantly over the 500 load cycles (−22%; p  = 0.001), but there was no significant change between the 5th and 200th load cycles. Lateral bending stiffness decreased significantly (−18%; p  = 0.009) over the 500 load cycles, but there was no significant change in axial rotation stiffness ( p  = 0.137). Group B: there was no significant difference between mean stiffness over the five freeze–thaw sequences in flexion/extension ( p  = 0.813) and a near-significant reduction in mean stiffness in axial rotation (−6%; p  = 0.07). However, there was a statistically significant increase in stiffness in lateral bending (+30%; p  = 0.007). Study findings indicate that comparison of in vitro testing results for immature thoracic bovine spine segments between studies can be performed with up to 200 load cycles without significant changes in stiffness. However, when testing protocols require greater than 200 cycles, or when repeated freeze–thaw cycles are involved, it is important to account for the effect of cumulative load and freeze–thaw cycles on spine segment stiffness.